Geneza i zarys psychologii kulturowej Floriana Znanieckiego - Chojniak, Arleta (Rocznik Pedagogiczny, 2021)
The aim of this paper is to present the cultural psychology project formulated by Florian Znaniecki. In the first part of the article, the authoress reconstructs the origin of this concept by reviewing the scholar’s early philosophical writings. In the second and third part of this paper, the authoress focus- es on presenting the basic categories of Znaniecki’s theory such as culture, culturalism and cultural action and highlights the role of cultural psychology in his scientific system.